'Becoming mainstream': the professionalisation and corporatisation of digital nomadism. (15th January 2020) - Aroles, Jeremy; Granter, Edward; de Vaujany, François‐Xavier
Abstract : Digital nomadism, a mobile lifestyle that encompasses a wide array of professional endeavours, ranging from corporate remote workers to digital entrepreneurs, has benefitted from a steadily growing appeal. Despite this, there is a dearth of research exploring the premises and development of digital nomadism. This paper is concerned with the image of digital nomadism, its underlying structure and practices, and its relation to the current world of work. In order to explore these aspects and problematise digital nomadism, the paper traces the development of digital nomadism and takes inspiration from the Deleuzo‐Guattarian image of the nomad. Adopting a qualitative approach to content analysis, this paper argues that digital nomadism is becoming increasingly institutionalised and professionalised, and, as such, is distant from the emancipatory dimension underlying its discourse and many of its cultural representations. Overall, digital nomadism appears as an extension of capitalist logics, rather than an alternative to them.